Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Silva Longobardi, Mauricio Miguel (2019)
This work seeks to analyze the internal and external environment of the Camposol company and its strategic business units, in order to define and implement strategies and create indicators that improve the performance and control of it. The initial chapter discusses the environment around it, identifying the impact of it and establishing the strengths and how they are used to create competencies. An analysis is carried out both globally and specifically by each of the strategic business units. It also identifies the main areas that generate value, analyzing the attributes that generate competitive advantage in the company. The second defined strategic objectives, proposed matrix-based strategies that would facilitate the achievement of these, the third chapter discussed the current organizational structure and proposed new strategic business units and restructuring of the organization, the closing chapter develops specific objectives and the success indicators of each.